Analysis of nitrite, organic acid content and bacterial community characteristics in naturally fermented sauerkraut soup of Inner Mongolia - XU Jianyang, CHEN Zhongjun, ZHANG Zuoyi, ZHAO Jin, SUN Ziyu, MANdlaa (Zhongguo niangzao)
The characteristics of nitrites, organic acids, and bacterial communities were analyzed in naturally fermented sauerkraut soup from 10 regions (numbered as HS, WLCB, CF, BT, BM, ALS, HM, ERDS, XAM and TL) in Inner Mongolia by high performance liquid chromatography (HPLC) and high-throughput sequencing technology, and the correlation analysis of the results was conducted. The results showed that the nitrite content in naturally fermented sauerkraut soup ranged from 0.04 to 0.28 mg/kg. Lactic acid was the organic acid with the highest content (1.97-46.45 mg/ml), while oxalic acid, formic acid, malic acid, acetic acid, citric acid, and fumaric acid showed significant differences among the samples (P<0.05). Moreover, Firmicutes and Proteobacteria were dominant bacterial phyla, while Lactobacillus and Pediococcus were dominant bacterial genera in the collected samples. Based on differences in community structure, 10 samples could be divided into three types. Correlation analysis showed that Lactococcus and Leuconostoc were significantly positively correlated with most bacterial genera (P<0.05), while Lactococcus, Leuconostoc and Weissella were significantly positively correlated with seven organic acids except for lactic acid and malic acid (P<0.05), and malic acid was significantly positively correlated with nitrite (P<0.05).